Subjetividades femininas: mulheres negras sob o olhar de Carolina Maria de Jesus, Maria Conceição Evaristo e Paulina Chiziane - Costa, Renata Jesus da (2008)
This dissertation studied the female subjects in the following literary masterpieces: Quarto de despejo: diário de uma favelada, published in 1960, written by the Brazilian Carolina Maria de Jesus, Ponciá Vicêncio, published in 2003, by the also Brazilian Maria Conceição Evaristo Brito, and Niketche: uma história de poligamia, published in 2004, by the southern Mozambiquean Paulina Chiziane. The opportunities which motivated their creation originated from the desire to support a debate about Black Women from the point of view of their partners. Based on that, it is possible to visualize a historical experience for those women, in which the prevailing factor is the importance of their daily art to survive: in contrast with representations formulated either by men or white women. The option to explore cultural spaces as well as distinctive historical periods reflects the attempt to avoid the crystallization of generic images of black female individuals, which form these authors narrative. Their perspective follow a new trend in women studies. In addition, because history and literature overlap in this study, it reveals the importance of the female writing as an open space for black and white women to reinvent their own identity